Determinan Kinerja Staf Akuntansi di RS PKU Muhammadiyah Surakarta - sugiarti, sugiarti (IAIN Surakarta, 2019)
The purpose of this study is to examine the influence of professionalism, organizational commitment, and job satisfaction to job performance. The sample of this study are 44 accounting staff in PKU Muhammadiyah Surakarta Hospital. With multiple regression analysis, the result of the research shows that professionalism and organizational commitment has significant effect to job performance. While job satisfication has no significant effect to job performance. Keywords: Professionalism, Organizational Commitment, Job Satisfaction, and Job Performance JEL Classification code: C21, C83, J28, J81